SUMOylation of Sox2 in neural stem cells - Marelli, Elisa (2018)
Sox2 plays a crucial role in the biology of neural stem cells (NSC) by regulating differentiation and keeping NSC in a slowly proliferative state which allows to maintain over time a pool of stem cells ready to differentiate in more rapidly dividing progenitor cells. Sox2 exerts these functions by transcriptionally activating and repressing target genes. At the present time, it is still not clear how these 2 opposite functions are regulated. Here, I analyse whether SUMOylation of Sox2 plays a role in the regulation of Sox2 activity and, ultimately, in the regulation of NSC biology.